The 175 best camp games : a handbook for leaders - Fraser, Kathleen, 1957-; Lum, Bernice; Fraser, Laura, 1985-; Fraser, Mary, 1983- (Erin, Ont. : Boston Mills Press, 2009)
Creative indoor and outdoor group activities with easy-to-follow instructions, for ages 4 to 16.
Break the ice -- Take it easy -- Get them moving -- Run them ragged -- Wet and wild.
Includes bibliographical references and index.
Keywords: Group games; Outdoor games; Indoor games